Conflict and recovery in Aceh : an assessment of conflict dynamics and options for supporting the peace process - Barron, Patrick; Clark, Samuel; Daud, Muslahuddin (World Bank, Washington, DC, 2012)
On August 15th the Government of Indonesia and the Free Aceh Movement (GAM) signed a Memorandum of Understanding aimed at ending almost 30 years of armed conflict in Aceh. This note summarizes the results of a rapid conflict assessment prepared by the Bank to understand conflict dynamics, to analyze possible scenarios after signing of the agreement, and to identify tools and mechanisms that the government, donors, and other stakeholders could use to support the peace process. The assessment was carried out from July 26 to August 19, 2005.